2010
DOI: 10.1007/s10549-010-1058-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical potential of the mTOR targets S6K1 and S6K2 in breast cancer

Abstract: Aim: The Mammalian Target of Rapamycin (mTOR) and its substrates S6K1 and S6K2 regulate cell growth, proliferation and metabolism through translational control. RPS6KB1 (S6K1) and RPS6KB2 (S6K2) are situated in the commonly amplified 17q21-23 and 11q13regions. S6K1 amplification and protein overexpression have earlier been associated with a worse outcome in breast cancer, but information regarding S6K2 is scarce. The aim of this study was to evaluate the prognostic and treatment predictive relevance of S6K1/S6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
65
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 47 publications
3
65
0
Order By: Relevance
“…[45][46][47] Amplification of eIF4E, S6K1, and cyclin D have been reported in adult cancers, including breast and mantle cell lymphomas but not in pediatric tumors. [48][49][50][51] mTOR-specific mutations in human cancer are extremely rare, with only two reported cases in adult carcinomas. [52] 3.…”
Section: Pi3k/akt/mtor Signaling In Cancermentioning
confidence: 99%
“…[45][46][47] Amplification of eIF4E, S6K1, and cyclin D have been reported in adult cancers, including breast and mantle cell lymphomas but not in pediatric tumors. [48][49][50][51] mTOR-specific mutations in human cancer are extremely rare, with only two reported cases in adult carcinomas. [52] 3.…”
Section: Pi3k/akt/mtor Signaling In Cancermentioning
confidence: 99%
“…miR-145 belongs to a subset of miRs whose expression is promoted by the interaction of microprocessor DICER (83) and zinc finger protein tristetraprolin (TTP) (Figure 4) (84). p70 S6 kinase (p70-S6K), a downstream effector of PI3K signaling (85) and frequently constitutively active in EOC disrupts this interaction by phosphorylating TTP and thus down-regulating expression of miR-145 (79). Metaanalysis in the Oncomine database has indicated that high levels of p70-S6K and low TTP levels are associated with ovarian cancer progression (79).…”
Section: Mir-138mentioning
confidence: 99%
“…Overexpression of the S6K1 gene and deregulated S6K1 signaling have been found in different malignancies, including breast, prostate, thyroid, brain and gastric cancers [13][14][15][16][17][18][19][20][21] that according to multiple studies correlate with poor prognosis of disease [14,[20][21][22]. However, implication of different S6K1 isoforms in carcinogenesis is poorly understood.…”
mentioning
confidence: 99%